Digital technology adoption, productivity gains in adopting firms and sectoral spill-overs: Firm-level evidence from Estonia - Mosiashvili, Natia (OECD Publishing, 2020)
With a newly constructed firm-level dataset combining various survey- and registry data from Statistics Estonia, this paper sheds new light on the labour productivity premium from adopting digital technologies and boosting digital skill use. The productivity premium is decomposed into a direct effect benefitting the firms actually increasing their digital intensity, and an indirect effect of belonging to a sector with high digital intensity. The firm-level productivity premium of being an adopting firm is consistently positive and sizeable across different digital technologies and measures of skill intensity. The evidence also suggests positive spill-over effects in manufacturing sectors and sectors with a high routine task content and thus a high automation potential
Keywords: Economics